2016
DOI: 10.4236/jmf.2016.61019
|View full text |Cite
|
Sign up to set email alerts
|

Burr Distribution as an Actuarial Risk Model and the Computation of Some of Its Actuarial Quantities Related to the Probability of Ruin

Abstract: In this paper, we have used an algorithm to fit the Burr XII distribution to a set of insurance data. As it is well known, the probability of ultimate ruin is obtained as a solution to an integro-differential equation and in case, the claim severity is distributed as Burr XII distribution, this equation has to be solved numerically to obtain an approximation to the probability of ultimate ruin. Two numerical algorithms, namely the stable recursive algorithm and the method of product integration have been used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…In both the cases, the Probability of ultimate ruin was found to be a decreasing function of the initial surpluses and this is expected, as larger initial surpluses should diminish the chance of ruin (if any) for the insurance company. The probability of ultimate ruin for the Burr XII distribution was computed through two numerical algorithms namely the stable recursive algorithm and the method of product integration in [13]. It is observed that there is deviation in the values obtained through these two algorithms and the Pollaczek-Khinchin formula.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In both the cases, the Probability of ultimate ruin was found to be a decreasing function of the initial surpluses and this is expected, as larger initial surpluses should diminish the chance of ruin (if any) for the insurance company. The probability of ultimate ruin for the Burr XII distribution was computed through two numerical algorithms namely the stable recursive algorithm and the method of product integration in [13]. It is observed that there is deviation in the values obtained through these two algorithms and the Pollaczek-Khinchin formula.…”
Section: Resultsmentioning
confidence: 99%
“…3) The simulation schemes need to be further improved for the values of the probability of ultimate ruin for the Burr XII distribution, it yielded are inconsistent to the values computed earlier [13]. 4) To avoid the complexity of having to evaluate a number of nested integrals numerically, we had to remain content with the evaluation of just the lower order convolution of these distributions, which, in turn, enabled us to compute the probability function for the number of claims until ruin, for a lower ranking whose significance to reality is not as important as the function, computed for a higher ranking of the order at which the claims arrive.…”
Section: Limitationsmentioning
confidence: 96%
See 2 more Smart Citations
“…Currently, one of the important examples of markets, which characterizing by the crowding out of some products by others that are more attractive from a technological point of view, is the market for information and telecommunication technologies (the market for data transmission services). For most managers of enterprises that are suppliers of products and investors, the issue of competitiveness of enterprises and their development prospects [1][2][3][4][5][6][7][8][9][10] and its prognosis [11][12][13] is relevant. The competitiveness of an enterprise is determined, first of all, by the quantity of manufactured products and sold, as well as the profit received.…”
Section: Introductionmentioning
confidence: 99%